Coproduction of Ethyl Acetate and n‐Butyl Acetate by Using a Reactive Dividing‐Wall Column. Issue 9 (8th August 2018) - Xie, Jiangwei; Peng, Fei; Li, Chunli; Jiang, Ting; Ma, Shuaiming
Abstract: The performance of the reactive distillation dividing‐wall column for coproduction of ethyl acetate and butyl acetate was experimentally studied. n ‐Butanol and ethanol are raw reaction materials that react with acetic acid in the reaction zone to produce n ‐butyl acetate and ethyl acetate, respectively. n ‐Butyl acetate is not only a product, but also acts to remove water generated by the esterification reactions. The effects of various parameters, such as catalyst loading per stage, reflux ratio, liquid split and molar feed ratios, ethyl acetate/ n ‐butyl acetate purity, pressure drop, and total energy consumption, are investigated. Results show that ethanol could be completely converted and the products could be easily separated, which shows great industrial application potential in the coproduction of ethyl acetate and n ‐butyl acetate. Abstract : Reactive distillation (RD) is a sustainable and energy‐ and cost‐efficient process for the coproduction of ethyl acetate and butyl acetate. The benefits of combining RD with a dividing‐wall column are revealed by studying a variety of factors experimentally and through simulations. Complete conversion of ethanol and easy product separation show great industrial application potential.